2012
DOI: 10.1111/j.1542-4758.2012.00756.x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effects of daily hemodialysis on vascular access outcomes: A prospective controlled study

Abstract: Background Daily hemodialysis has been associated with surrogate markers of improved survival among hemodialysis patients. A potential disadvantage of daily hemodialysis is that frequent vascular access cannulations may affect long term vascular access patency. Methods The study design was a four-year, non-randomized, contemporary control, prospective study of 77 subjects in either 3 hour daily hemodialysis (6 dialysis treatments weekly of 3 hours each; n = 26) or conventional dialysis (3 dialysis treatments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 32 publications
0
5
0
2
Order By: Relevance
“…Achinger et al demonstrated no change in vascular access adverse event rate with extended‐hours compared to conventional hemodialysis (incident rate ratio 0.74, 95% CI 0.40 to 1.36, P = 0.33) . Vascular access events were reported for a further non‐randomized trial, however data were unable to be synthesized.…”
Section: Resultsmentioning
confidence: 98%
“…Achinger et al demonstrated no change in vascular access adverse event rate with extended‐hours compared to conventional hemodialysis (incident rate ratio 0.74, 95% CI 0.40 to 1.36, P = 0.33) . Vascular access events were reported for a further non‐randomized trial, however data were unable to be synthesized.…”
Section: Resultsmentioning
confidence: 98%
“…Nineteen studies met the inclusion criteria [4,5,7,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25]. Three studies were excluded because the vascular access event rates were not reported [26,27] or because of missing demographic data [28].…”
Section: Resultsmentioning
confidence: 99%
“…La durée moyenne de la formation était de 35 jours (35)(36)(37)(38)(39)(40)(41)(42). Dix patients (83%) ont été installés à domicile.…”
Section: Programme De La Formation Des Patientsunclassified